SPATIAL DISTRIBUTION OF Thunnus.sp, VERTICAL AND HORIZONTAL SUB-SURFACE MULTILAYER TEMPERATURE PROFILES OF IN-SITU AGRO FLOAT DATA IN INDIAN OCEAN - Agus Hartoko (JOURNAL OF COASTAL DEVELOPMENT, 2010)
The study was the first ever attempt in fisheries oceanography sciences to explore the empiric correlationbetween the spatial distribution of tuna (Thunnus.sp) and sub-surface in-situ temperature data. By means ofoptimalization and use of an in-situ data of both vertical and horizontal which will be processed into amultilayer subsurface seawater temperature of ARGO Float in Indian ocean. So far only sea surfacetemperature (with temperature around 29 °C) data were used to look for the correlation for tuna spatialdistribution, while the Thunnus.sp swimming layer as widely known is in about 80 – 250m depth withseawater temperature between 15 – 23 °C. The noble character of ARGO Float data is as in-situ datarecorded directly by the sensors, transmitted to the satellite, transmitted to the ground station and ready to beused by researcher all over the world.In the study, about 216 seawater temperature coordinates of ARGOFloat and actual tuna catch data in the same day were used to represent the dry season (April – November2007) analysis, and about 90 data were used for the rainy season (December – March 2007). The actualtuna catch and its coordinates data were collected with permission from PT. Perikanan Samudra Besar,(PT.PSB) Benoa – Bali Indonesia. Then both seawater temperature and tuna data were processed using aKrigging method or spatial interpolation method.Based on a monthly actual tuna production by fishing fleetof PT.PSB operated in Indian Ocean indicates that there were two cycles of low catch in March and July andhigh catch in May and December 2007. In general, seawater temperature in depth of 80m, 100m, 150m and200m of the dry season was 2 °C warmer than those of the rainy season. Range of seawater temperature willdecrease due to the water depth, range of seawater temperature at depth of 150m was between 14 – 22 °Cand at depth of 200m between 12 – 20 °C. Based on the regression and correlation between tuna catch andseawater temperature revealed that seawater temperature at depth 150m has the highest coefficient ofcorrelation than to the seawater temperature at depth 100m and 200m.